Coordination chemistry of 2,4,6-tri(pyridyl)-1,3,5-triazine ligands - Therrien, Bruno (My University, 2011)
This review covers the rich coordination chemistry of 2,4,6-tri(pyridyl)-1,3,5-triazine ligands. These polypyridyl derivatives have been coupled to transition metals and lanthanides, and the complexes obtained have been used in various fields such as luminescent materials, for the preparation of coordination polymers and networks as well as for the synthesis of discrete metalla-assemblies. The synthetic and structural aspects of the different isomers of 2,4,6-tri(pyridyl)-1,3,5-triazine are presented, and a survey of their coordination chemistry is given.
Keywords: Coordination polymers; Metal–organic frameworks; Multidentate ligands; Polypyridyl ligands; Porphyrin arrays; Supramolecular assemblies